Genetics of OCD - Nestadt, Gerald (2010)
SYNOPSIS: OCD is a common debilitating condition affecting individuals from childhood through adult life. There is good evidence of genetic contribution to its etiology, but environmental risk factors also are likely to be involved. The condition probably has a complex pattern of inheritance. Molecular studies have identified several potentially relevant genes, but much additional research is needed to establish definitive causes of the condition.